Encapsulation and Biological Activity of Hesperetin Derivatives with HP-β-CD - Anna Sykuła; Agnieszka Bodzioch; Adriana Nowak; Waldemar Maniukiewicz; Sylwia Ścieszka; Lidia Piekarska-Radzik; Elżbieta Klewicka; Damian Batory; Elżbieta Łodyga-Chruścińska (Molecules, 2023)
The encapsulation of insoluble compounds can help improve their solubility and activity. The effects of cyclodextrin encapsulation on hesperetin’s derivatives (HHSB, HIN, and HTSC) and the physicochemical properties of the formed complexes were determined using various analytical techniques. The antioxidant (DPPH•, ABTS•+ scavenging, and Fe2+-chelating ability), cytotoxic, and antibacterial activities were also investigated. The inclusion systems were prepared using mechanical and co-evaporation methods using a molar ratio compound: HP-β-CD = 1:1. The identification of solid systems confirmed the formation of two inclusion complexes at hesperetin (CV) and HHSB (mech). The identification of systems of hesperetin and its derivatives with HP-β-CD in solutions at pHs 3.6, 6.5, and 8.5 and at various temperatures (25, 37 and 60 °C) confirmed the effect of cyclodextrin on their solubility. In the DPPH• and ABTS•+ assay, pure compounds were characterized by higher antioxidant activity than the complexes. In the FRAP study, all hesperetin and HHSB complexes and HTSC-HP-β-CD (mech) were characterized by higher values of antioxidant activity than pure compounds. The results obtained from cytotoxic activity tests show that for most of the systems tested, cytotoxicity increased with the concentration of the chemical, with the exception of HP-β-CD. All systems inhibited Escherichia coli and Staphylococcus aureus.